Előttem az élet . What Lies Ahead - Groó, Diana (Filmpartners Ltd., 2006)
Verzio FF submission “As soon as you enter this special school, we are in a different world full of miracles. We learn that the disabled protagonists of this film live their everyday lives in the most natural way. Confronted with their openness, joy and understanding, we realize that we are the ones who build boundaries around ourselves and create stereotypes. For them the term “otherness”, and prejudice against people who are different, simply do not exist. They struggle tirelessly every single day to achieve something that people without disabilities take for granted: to make a move, a step. And when they overcome their difficulties these young people give a new meaning to perseverance and positive thinking.” Diána Groó